Characterizing and Analyzing Sonor System in South Sumatra Tidal Wetlands - Elisa Wildayana; M. Edi Armanto; M.S. Imanudin; Heri Junedi (Center for Journal Management and Publication, 2017)
The research aimed to (1) describe changing biomass during the burning process, (2) characterize the nutrient loss due to biomass burning, (3) analyse the financial loss of nutrient transfer, and (4) compare farmer’s income among three land typologies. This research was conducted in tidal wetlands Talang Sepucuk, OKI District, South Sumatra with a slope of 0-3 %. Three selected land typologies (B, C and D) are located in the area adjacent to one another with distance < 1.200 m. The natural vegetation data and paddy yields was recorded by squares method, i.e. 25 x 25 m at each study site, dried and weighed and analyzed in the laboratory. The research resulted that the nutrient transfer due to biomass burning was in range of Rp 49.98-51.62 Mills/ha/year. The farmer’s income of the sonor system was very small (Rp 3.61-3.97 Mills/ha/year), it was only about 7 % of the total financial loss of nutrient transfer). The remaining value (93 %) is beyond the capacity of farmers to harvest natural resources. This value (93 %) is classified as one of the biggest negative impact of the sonor system to be paid by the all people. The government must intervene to make the public policy by giving direct subsidy to farmers NOT to burn biomass in the sonor system with compensation of at least 2 (two) times of farmer’s income from the sonor system (around Rp 7.66 Mill. Rp/ha/year). If farmers still continue to apply the sonor system by using fire, then there is very little opportunity for us to manage the nutrients loss due to biomass burning. The preventive and proactive approach is the best way how to manage the land resources.